2015
DOI: 10.1177/1559827615611024
|View full text |Cite|
|
Sign up to set email alerts
|

Improved Cardiovascular Parameter With a Nutrient-Dense, Plant-Rich Diet-Style: A Patient Survey With Illustrative Cases

Abstract: . The results presented from a practice survey include cases of interest, demonstrating improvements in cardiometabolic risk factors utilizing a Nutrient-Dense, Plant-Rich (NDPR) diet. It includes changes in weight, blood pressure, and lipids parameters derived from the survey and retrospective chart review. . Practice records and interviews were used for case history descriptions. Participants' data were collected via an online survey.. Adherence to a NDPR dietary protocol resulted in reduced low-density lipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Recent systematic review and meta-analysis of 30 observational studies and 19 clinical trials that examined associations between PBDs and plasma lipids showed that the consumption of vegetarian diets, particularly vegan diets, is associated with lower levels of plasma lipid, but not with decreased triglycerides compared with omnivorous diets in observational studies and clinical trials (5). In a nonrandomized study (without a control group) on 328 obese people who were not taking cholesterol-lowering medications, Fuhrman and Singer showed that in a 1-year plant-based intervention the average drop of LDL-cholesterol was 25% (from 4.4 to 3.3 mmol/L) and that triglycerides decreased by 40% (from 2.3 to 1.4 mmol/L), while the total cholesterol change for the interventional group was not reported (15). Our results extend this finding by showing a further meaningful reduction of LDL-cholesterol in participants with marginally elevated baseline cholesterol, even in the subsample of participants with normal BMI.…”
Section: Discussionmentioning
confidence: 99%
“…Recent systematic review and meta-analysis of 30 observational studies and 19 clinical trials that examined associations between PBDs and plasma lipids showed that the consumption of vegetarian diets, particularly vegan diets, is associated with lower levels of plasma lipid, but not with decreased triglycerides compared with omnivorous diets in observational studies and clinical trials (5). In a nonrandomized study (without a control group) on 328 obese people who were not taking cholesterol-lowering medications, Fuhrman and Singer showed that in a 1-year plant-based intervention the average drop of LDL-cholesterol was 25% (from 4.4 to 3.3 mmol/L) and that triglycerides decreased by 40% (from 2.3 to 1.4 mmol/L), while the total cholesterol change for the interventional group was not reported (15). Our results extend this finding by showing a further meaningful reduction of LDL-cholesterol in participants with marginally elevated baseline cholesterol, even in the subsample of participants with normal BMI.…”
Section: Discussionmentioning
confidence: 99%
“…It was also reported by the majority of subjects that the previous dietary change affected their physical or mental well-being, with virtually all the subjects reporting a positive change. This finding is likely due to consuming more foods from whole plant sources than the previous diet, such as fruits, vegetables, whole grains, and legumes (as well as the synergistic effects of eating the varieties together), which is related to a healthier dietary profile of protein and fat (with little to no dietary cholesterol in the case of the vegan diet), folate, fiber and complex carbohydrates, phytochemicals, and especially antioxidants [ 78 , 91 ].…”
Section: Discussionmentioning
confidence: 99%
“…This micronutrient-dense, plant-rich diet (mNDPR), the dietary pattern utilized in this study, has been proven to be safe and effective in clinical applications not only with inflammation reduction [ 5 ], but also with weight reduction and blood pressure lowering [ 6 ], lipid management [ 7 , 8 ], glycemic control in diabetes [ 9 ], perceptions of hunger [ 10 ], precautionary approaches for cancer [ 11 ], and overall health and longevity [ 12 ].…”
Section: Introductionmentioning
confidence: 99%